Career choices made for the hospital medical specialties by graduates from UK medical schools, 1974-2005. - Goldacre, M; Lambert, T; Laxton, L (2009)
This article summarises findings from studies of career choices made for the hospital medical specialties by medical graduates one, three and five years after qualifying from UK medical schools in selected years from 1974 to 2005. The percentage of doctors who, early in their careers, expressed a preference for the hospital medical specialties declined between the 1970s and 1980s, increased during the 1990s, and has stabilised since then. The percentage of women medical graduates who want a career in the hospital medical specialties is now similar to that of men. Compared with doctors who choose other specialties, a higher percentage of doctors who choose the hospital medical specialties are uncertain about their specialty choice in the early years after qualification. This uncertainty needs to be considered by those planning postgraduate medical education for the hospital medical specialties, particularly now that postgraduate training in the UK has become much more structured.